The Importance of Maqashid Sharia as a Theory In Islamic Economic Business Operations - Nurhadi, Nurhadi (Faculty of Islamic Economics and Business of Institut Agama Islam Negeri (IAIN) Pekalongan, 2019)
This article discusses the urgency of maqashid wisdom in the operation of Islamic economic business. The rapid development of Islamic economics and finance in the contemporary era, many problems have arisen, such as hedging, sukuk schemes, repos, syndicated financing between Islamic banks or with conventional banks, restructuring, indent property financing, ijarah maushufash fiz zimmah, multi financing use, credit card design, maqashid from annuity, bargain, net revenue sharing, gold installments, gold investment and other new cases. The application of the wisdom of the maqashid shari`ah is an elaboration of the great maqashid (goal), namely hifzu al-Mal (safeguarding wealth) and fulfilling the purpose and mashlahah of wealth. Maintaining and maintaining the intentions of these assets sometimes in terms of how to get it (min janibi al-wujud) or in terms of maintaining assets that are already owned (min janibi al-?adam). Hifzu al-Mal is a family of methods in the field of muamalah, this method is translated by Maqashid syari`ah ammah (general purposes) and Maqashid khassah (special purpose) also called maqashd juz?iyyah, which is very numerous and countless. Maqashid khassah is the result of Istiqra 'of the scholars towards the texts and the laws of shari'ah and results in certainty (qath'i) that this Shari'a establishes it as a goal that has consequences and implications. So in the operation of sharia economic business the wisdom of maqashid sharia is that the benefit must be secured and based on shariah principles, even though the Islamic economic business transactions by establishing the benefits that are in accordance with the sharia and the proposition as well as the interfaith of the minkum (the pleasure of the same pleasure) in accordance with the sharia agreement, even though the law is debated, for example bai ad-dayan contract, bargaining contract and others.